A temporal shift of chondrule generation from the inner to outer Solar System inferred from oxygen isotopes and Al-Mg chronology of chondrules from primitive CM and CO chondrites. (1st April 2022) - Fukuda, Kohei; Tenner, Travis J.; Kimura, Makoto; Tomioka, Naotaka; Siron, Guillaume; Ushikubo, Takayuki; Chaumard, Noël; Hertwig, Andreas T.; Kita, Noriko T.
Abstract: Deciphering the spatial and temporal evolution of chondrules allows for a better understanding of how asteroidal seeds formed, migrated, and eventually accreted into parent asteroids. Here we report high precision Al-Mg ages and oxygen three-isotope ratios of fifteen FeO-poor chondrules from the least metamorphosed Mighei-like (CM) and Ornans-like (CO) carbonaceous chondrites, Asuka 12236 (CM2.9), Dominion Range 08006 (CO3.01), and Yamato 81020 (CO3.05). This is the first report of Al-Mg ages of chondrules from the CM chondrite group. All but one of the fifteen chondrules exhibit a restricted range of inferred initial 26 Al/ 27 Al ratios, and all ratios are ≤ 6.0 × 10 −6, which is systematically lower than those of the majority of ordinary chondrite (OC) chondrules. These observations indicate that the majority of chondrules in the outer Solar System were produced ≥2.2 Ma after the formation of Ca-Al-rich inclusions (CAIs), which postdates OC chondrule formation in the inner Solar System (≤2.2 Ma after CAI formation). We propose that the discrete chondrule-forming events in different disk regions reflect a time difference in growth and orbital evolution of planetesimals within the first 4 Ma of the Solar System. One chondrule from Asuka 12236 has an age of 1.9 Ma after CAI formation and is therefore significantly older than the other fourteen chondrules, meaning this chondrule formed contemporaneously with the majority of OC chondrules. This old chondrule also exhibits 16 O-depleted oxygen isotope characteristics compared to the other chondrules, suggesting a distinct formation region, probably inside the disk region relative to where the majority of CM and CO chondrules formed. Our results indicate that this old chondrule has migrated from the inner to the outer part of the protoplanetary disk within ∼1 Ma and then accreted into the CM parent asteroid >3 Ma after CAI formation, although its formation exterior to the accretion region of the CM parent asteroid and subsequent inward migration cannot be ruled out completely.